Trends in the epidemiology of severe pediatric non-surgical renal disorders in Ibadan Nigeria: A marked increase in the incidence of acute kidney injury (2016)
Background: Renal disorders are increasingly being recognized as major contributors to morbidity and mortality. Variability in their pattern in different populations and regions of the world and changes occurring with time have been demonstrated. We aimed to determine the current trends in the pattern of severe non-surgical childhood renal disorders at our Centre and compare the findings with previous studies. Methodology: A descriptive analytical study was carried out on consecutive incident cases of nonsurgical renal disorders aged 14 years and below, managed in the Pediatric Nephrology Unit of the University College Hospital, Ibadan, Nigeria. Two separate time periods were studied. Results: A total of 869 incident cases of severe non-surgical disorders were admitted during the study periods. There was an increase in the hospital incidence from 1.5 to 2.2 per 100 pediatric admissions and in the average yearly admission from 43 to 103. The crude annual incidence increased from 42 per million age-related population (PMARP) to 86 (PMARP) at the end of the two study periods. The most remarkable increase occurred with Acute Kidney Injury, which showed a 6.5-fold rise and was the most common cause of renal morbidity and mortality in children encountered in the study. Interventional measures resulted in early detection, prompt treatment and reduced mortality. Conclusion: The study has shown an increase in the incidence of severe childhood renal disorders in Ibadan, with Acute Kidney Injury being the leading non-surgical renal disorder. A significant decline in case fatality rates was demonstrated in recent years.